2022
DOI: 10.3389/fpls.2022.846937
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Genome-Wide Location-Specific Polymorphic SSR Marker Discovery in Black Pepper by GBS Approach

Abstract: Black pepper (Piper nigrum), the “King of Spices,” is an economically important spice in India and is known for its medicinal and cultural values. SSRs, the tandem repeats of small DNA sequences, are often polymorphic in nature with diverse applications. For population structure, QTL/gene discovery, MAS, and diversity analysis, it is imperative to have their location specificity. The existing PinigSSRdb catalogs ~70K putative SSR markers but these are anonymous (unknown chromosomal location), based on 916 scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Furthermore, the grouping of polymorphic SSRs based on the five classes of perfect SSRs and compound SSRs showed that the dinucleotides were dominant. The higher tendency of dinucleotide SSRs to be polymorphic is consistent with other studies on genomic SSRs in apples ( Silfverberg-Dilworth et al., 2006 ), peanuts ( Zhao et al., 2012a ), watermelon ( Zhao et al., 2012b ), and black pepper ( Negi et al., 2022 ). However, in a previous study where a repeat-rich genomic library screening method was used to generate SSR markers, the compound SSRs were found to be more polymorphic in cashew ( Croxford et al., 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the grouping of polymorphic SSRs based on the five classes of perfect SSRs and compound SSRs showed that the dinucleotides were dominant. The higher tendency of dinucleotide SSRs to be polymorphic is consistent with other studies on genomic SSRs in apples ( Silfverberg-Dilworth et al., 2006 ), peanuts ( Zhao et al., 2012a ), watermelon ( Zhao et al., 2012b ), and black pepper ( Negi et al., 2022 ). However, in a previous study where a repeat-rich genomic library screening method was used to generate SSR markers, the compound SSRs were found to be more polymorphic in cashew ( Croxford et al., 2006 ).…”
Section: Discussionsupporting
confidence: 90%
“…Genetic diversity in the sampled accessions of P . nigrum was relatively low compared to the previous genetic analyses carried out using RAPD [ 11 ], AFLP [ 13 ], and SSR [ 15 , 18 ] markers. The accessions used in this study were those in cultivation at present, which have been subjected to different selective pressures, particularly for improved yield and quality characteristics.…”
Section: Discussionmentioning
confidence: 62%
“…Using this reference genome, 50 genome-wide SSR markers were developed that discriminated 30 Indian black pepper landrace accessions in four distinct clusters [ 17 ]. More recently, Negi et al [ 18 ] characterized chromosomal location-specific polymorphic SSRs from 29 Indian black pepper accessions, with potential application in diversity analysis. Although SSR markers have been the most widely used for assessing the genetic diversity of crops, the characterization of large germplasm collections by this method could be time-consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The first P. nigrum reference genome data and its assembly were reported recently (Hu et al, 2019), providing an evolutionary perspective and insight into the metabolic processes and molecular basis of species-specific Piperine biosynthesis. Very recently, a comprehensive web-genomic resource of black pepper was developed by (Negi et al, 2022), which catalogues genome-wide deep mining of SSR markers from the genome assembly of black pepper. Studies on the identification of putative biotic and abiotic stress-associated genes by transcriptomics sequencing approaches (Hao et al, 2016) (Negi et al, 2021), have produced important basic information and serve as valuable resources for future breeding programmes.…”
Section: Introductionmentioning
confidence: 99%